Corporate Fraction and the Equilibrium Term Structure of Equity Risk - Marfè, Roberto (Review of Finance, 2016)
Abstract The recent empirical evidence of a downward-sloping term structure of equity risk is viewed as a challenge to many leading asset pricing models. This article analytically characterizes conditions under which a continuous-time long-run risk model can accommodate the stylized facts about dividend and equity risk, when dividends are a stationary stochastic fraction of aggregate consumption. Such a cointegrating relation not only makes dividends riskier in the short run than at medium horizons but also preserves the role of long-run risk: consequently, the model captures both the traditional puzzles, like the high equity premium, as well as the new evidence about the term structure of equity risk.